Unraveling the mystery of recent shortened response time of ENSO to Atlantic forcing - Qi Tian; Jin-Yi Yu; Hyacinth C. Nnamchi; Tim Li; Jianping Li; Xichen Li; Ruiqiang Ding (Nature Communications)
Abstract The El Niño-Southern Oscillation (ENSO) is known to respond to tropical Atlantic (TA) sea surface temperature (SST) forcing. However, the response time of ENSO to the TA SST forcing is not stationary but varies over decades, the reasons for which remain poorly understood. Here we show that decadal changes in ENSO’s response time to TA SST forcing are primarily influenced by the south-north shift of the dominant mode of TA SST variability itself. Before the mid-1980s, the southward-shifted TA mode prolongs the response time to ~20 months through an eastward-propagating mid-latitude teleconnection. In contrast, when the TA mode shifts northward after the mid-1980s, the response time decreases to 6–9 months via a faster westward-propagating subtropical teleconnection. Our findings underscore the importance of considering the meridional shift of the TA mode when understanding the impacts of the TA SST variability on ENSO, which has profound implications for ENSO forecasting.